Prevalence of Self-Regulated Learning in MBKM Program Students - Saputra, Nur Mega Aris; Hidayah, Nur; Ramli, M.; Arip, Mohammad Aziz Shah Mohamed (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Contextual changes in the learning process are one of the problems faced by students who start participating in the MBKM program. Self-regulated learning contributes to students being able to regulate their own learning so that students can achieve optimal results in implementing the MBKM program. The purpose of this study was to analyze the prevalence of self-regulated learning in generation Z students in the context of implementing the MBKM program. The research method used was quantitative research with a survey design. The sampling technique used stratified random sampling on MBKM students in the guidance and counselling department with a total sample of 57 MBKM program students. The data collection instrument was an independent learning scale. The analysis of the research data used descriptive analysis. The results of the study showed that most students who were generation Z had a level of self-regulated learning with moderate criteria or even fell into the low criteria category. The differences in the three indicators or dimensions of self-regulated learning showed no significant differences. Based on the results of this study, recommendations were provided for mentoring before the implementation of the MBKM program.